Determinan Turnover Intention Pada Perawat Bakti Timah Medika - Muchtadin, Muchtadin; Sundary, Zelvy Emmelya (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2024)
Background: Nurse turnover intention is a problem in the health service sector throughout the world because it is related to the large costs incurred by hospitals and the decline in the quality of health service human resources. Aims: This research is aimed at finding out the magnitude of the impact that learning agility, job satisfaction and work stress have on the turnover intention of Bakti Timah Medika nurses. Methods: The research design is quantitative causality. The number of respondents was 82 nurses taken using convenience sampling. SEM-PLS is used as a data analysis method. Results: The findings in this study show that job satisfaction has a significant negative effect on turnover intention, while work stress has a significant positive effect on turnover intention. Learning agility was found to have no effect on nurse turnover intention. Conclusion: Future researchers can use mediating variables such as job stress and job satisfaction to explain the influence of learning agility on turnover intention which is not significant in nurses. Management must further increase nurses' job satisfaction through increasing salaries and benefits, creating a comfortable work environment, improving nurses' welfare, improving the hospital management system. Management must pay attention to nurses' work stress by providing freedom in determining work schedules, reducing workload by adding personnel. In the end, all of these things are useful for reducing nurse turnover intention.